2020
DOI: 10.4236/aid.2020.103014
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentations of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, emerged in Wuhan, China in December 2019. It has now spread to all parts of the world and as of 26 th July 2020, more than 16 million cases and over 600,000 deaths have been reported. The commonest presentation is respiratory in nature with non-productive cough, fever and shortness of breath. Some COVID-19 patients have had atypical or unusual presentations involving the neurological, metabolic, gastrointestinal, renal, haematological, cutaneous and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…1 – 4 Common symptoms of COVID-19 include fever, dry cough, and tiredness. 5 , 6 A subset of patients develops a more severe form of disease, characterized by acute respiratory distress syndrome (ARDS), and hematological, neurological, cardiac, and renal complications. 7 – 9 Many hematological findings have been reported in COVID-19 patients, and this review summarizes the reported hematological abnormalities (changes in platelet, white blood cell, and hemoglobin levels, and coagulation/fibrinolytic alterations), explores their patho-mechanisms, and discusses its management.…”
Section: Introductionmentioning
confidence: 99%
“…1 – 4 Common symptoms of COVID-19 include fever, dry cough, and tiredness. 5 , 6 A subset of patients develops a more severe form of disease, characterized by acute respiratory distress syndrome (ARDS), and hematological, neurological, cardiac, and renal complications. 7 – 9 Many hematological findings have been reported in COVID-19 patients, and this review summarizes the reported hematological abnormalities (changes in platelet, white blood cell, and hemoglobin levels, and coagulation/fibrinolytic alterations), explores their patho-mechanisms, and discusses its management.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of various types of cutaneous symptoms is one of the frequent reported extrapulmonary manifestations in coccidioidomycosis. Several studies have documented skin findings associated with COVID-19 viral infection, similar to that of cutaneous manifestations seen in patients affected with coccidioidomycosis [ 2 - 4 ]. The pathophysiology involves either a hypersensitivity reaction as part of the immune response, direct inoculation or dermatomal dissemination [ 5 ].…”
Section: Discussionmentioning
confidence: 98%
“…The renin-angiotensin system (RAS) plays a major role in liver inflammation, tissue remodeling, and fibrosis. Angiotensin-converting enzyme 2 is a key negative regulator of the RAS and limits fibrosis through the degradation of Angiotensin II and the formation of Angiotensin (1)(2)(3)(4)(5)(6)(7). Upon binding of the SARS-CoV-2 virus, ACE2 is endocytosed and levels are reduced on the cell surface.…”
Section: Bilirubin Levelmentioning
confidence: 99%
“…5 Although fever and respiratory symptoms predominate in coronavirus infections, a range of liver manifestations is seen in SARS-CoV-1, MERS, and SARS-CoV-2 patients. 6,7 Table 1 shows a summary of the liver findings in SAR-CoV-1, MERS, and SARS-CoV-2. 6,[8][9][10][11][12][13][14][15][16][17] Hepatic impairment was seen in up to 60% of patients with SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%